Revisiting the Role of TRP, Orai, and ASIC Channels in the Pulmonary Arterial Response to Hypoxia - Reyes, Roberto V.; Castillo-Galán, Sebastián; Hernandez, Ismael; Herrera, Emilio A.; Ebensperger, Germán; Llanos, Aníbal J. (Frontiers in Physiology, 2018)
The pulmonary arteries are exquisitely responsive to oxygen changes. They rapidly and proportionally contract as arterial PO2 decrease, and they relax as arterial PO2 is re-established. The hypoxic pulmonary vasoconstriction (HPV) is intrinsic since it does not requires neural or endocrine factors, as evidenced in isolated vessels. On the other hand, pulmonary arteries also respond to sustained hypoxia with structural and functional remodeling, involving growth of smooth muscle medial layer and later recruitment of adventitial fibroblasts, secreted mitogens from endothelium and changes in the response to vasoconstrictor and vasodilator stimuli. Hypoxic pulmonary arterial vasoconstriction and remodeling are relevant biological responses both under physiological and pathological conditions, to explain matching between ventilation and perfusion, fetal to neonatal transition of pulmonary circulation and pulmonary artery over-constriction and thickening in pulmonary hypertension. Store operated channels (SOC) and receptor operated channels (ROC) are plasma membrane cationic channels that mediate calcium influx in response to depletion of internal calcium stores or receptor activation respectively. They are involved in both HPV and pathological remodeling since their pharmacological blockade or genetic suppression of several of the Stim, Orai, TRP or ASIC proteins in SOC or ROC complexes attenuate the calcium increase, the tension development, the pulmonary artery smooth muscle proliferation and pulmonary arterial hypertension. In this minireview, we discuss evidence obtained in in-vivo animal models, at the level of isolated organ or cells of pulmonary arteries , and we identify and discuss questions for future research needed to validate these signaling complexes as targets against pulmonary hypertension.